On the Heterogeneity in Longevity among Socioeconomic Groups: Scope, Trends, and Implications for Earnings-Related Pension Schemes - Mercedes Ayuso; Jorge Miguel Bravo; Robert Holzmann (Institute for the Study of Labor (IZA), 2016)
Heterogeneity in longevity between socioeconomic groups is increasingly documented for developed economies and is reviewed in the paper. Heterogeneity in life expectancy disaggregated by main socioeconomic characteristics – such as age, gender, race, health, education, profession, income, and wealth – is sizable and has not declined in recent decades. The prospects for future decline are not strong, either; perhaps even to the contrary. As heterogeneity is closely linked to income or earnings (i.e., the contribution base of earnings-related social programs such as pensions) and as heterogeneity is empirically sizable, the result is major implicit taxes for some groups – particularly the less educated and low earners – and major subsidies for other groups – particularly highly educated individuals and high-income earners. The implications for pension reform and scheme design are substantial as taxes/subsidies counteract the envisaged effects of (i) a closer contribution-benefit link, (ii) a later formal retirement age to address population aging, and (iii) more individual funding and private annuities to compensate for reduced public generosity.
Keywords: D9; G22; H55; J13; J14; J16; 330; implicit subsidy; life expectancy; gender; lifetime income; implicit tax